Pre-enrolment interviews designed to communicate program requirements. - Wood, Denise; Bailey, Robyn (Australia. Dept of Education and Training (DET), 2018)
The research project on which this case study is based involved qualitative research undertaken with a randomly selected sample of 124 CQUniversity undergraduate nursing students commencing the first term of their first year of study. The case study for project SP14-4602 focused on semi-structured phone interviews with a purposive sub-sample of six of the 124 students from the larger study and six staff members who were either directly involved in lecturing first year students or in a support role of students. The findings of this case study suggest that a pre-commencement interview assisted students in that they were more aware of inherent requirements as well as having a better understanding of the requirements of the program itself. The findings also show that the staff interviewed believed that the students who received the pre-commencement interview were better prepared. The findings are consistent with the findings from the larger project on which the case study was based. A summary of the case study is also available, published as: Early people-rich interventions improve transition and first year retention.